Comprehensive genetic screening of 70 severe adolescent idiopathic scoliosis probands reveals novel pathogenic variants and syndromic associations - Horbacz, Monika; Koczkowska, Magdalena; Rocławski, Marek; Ceynowa, Marcin; Madanecki, Piotr; Sarkisyan, Daniil; Mieczkowski, Jakub; Śledzińska, Karolina; Dumanski, Jan P.; Pankowski, Rafał; Piotrowski, Arkadiusz (Frontiers in Medicine, 2025)
IntroductionIdiopathic scoliosis (IS) is a complex spinal deformity affecting 3% of the population, with a multifactorial and genetically heterogeneous origin. This study aimed to investigate the genetic origins of severe IS by examining both constitutional and post-zygotic alterations.MethodsWe analyzed 70 unrelated IS-affected individuals using whole exome sequencing (WES) and SNP array approaches on intraoperatively collected articular processes and blood samples.ResultsTwo pathogenic constitutional copy number variants (CNVs) were identified – a 43.6 Mb duplication on chromosome 8p and trisomy X – along with eight regions of homozygosity (ROH) located on chromosomes 1, 2, 8, 12, 14, and 16, absent in ethnically matched controls. Additionally, a heterozygous DMD deletion (exons 17–36) was found in one female, and rare recurrent pathogenic single-nucleotide variants (SNVs) were detected in ENAM and FLNB genes. Notably, 13% (95% CI, 6.1–23%) of individuals harbored pathogenic variants, spanning CNVs, ROH, and SNVs, suggesting a genetic contribution to IS.DiscussionOur findings demonstrate that one in seven cases classified as idiopathic may have an underlying monogenic cause. This study underscores the polygenic and heterogeneous nature of IS and highlights the need for genetic testing by integrating WES and SNP array analyses into its diagnostic workflow. Our findings suggest that incorporating genetic testing into the diagnostic evaluation of severe IS patients may enable personalized genetic counseling and, consequently, improve clinical management.